Clinico-Etiological Profile of New Onset Seizures in Gaeriatric Patients at a Tertiary Care Hospital (Academia Journal of Medicine, 2020)
Background: Seizure is defined as “a paroxysmal event due to abnormal excessive or synchronous neuronal activity in the brain.” Based on  discharge characteristics and its distribution, this unusual activity can manifest either as focal or generalized tonic clonic to absence seizures  which are not easily noticeable by observer. For 2010, as indicated by the Global Burden of Disease (GBD) investigation, epilepsy accounted  for 0.7% of burden globally i.e, more than 17 million DALYs. Studies conducted in India have reported variable incidence rates which varies  from 0.2 to 0.6 per 1,000 population. The incidence rates reported from India are similar to most of the developed countries and less than most  of the developing nations which ranged from 1.0 to 1.9 per 1,000 per year. AIM: The aim of the study is to assess & identify the various  clinico-etiological factors causing first onset of seizures in gaeriatric patients. Rationale: Several studies are available on seizure in elderly in  western population but very few studies are done in this part of the world. Etiological profile of seizures varies from place to place because of  difference in socio-economic and cultural attributes, prevalence of various diseases in a particular area and several other factors. This study  aims to observe the clinico-etiological profile of new onset seizures in elderly in Moradabad region of western Uttar Pradesh. Subjects and  Methods: This study was carried out at Teerthanker Mahaveer Medical College and Research Centre, Moradabad (UP) as an observational  hospital based study. 51 patients of new onset seizures above 60 years of age. Inclusion Criteria: All patients with new onset seizures and were  more than 60 years of age. Exclusion Criteria: All patients with age less than 60 years. All known cases of Seizure disorder/Epilepsy were  excluded. All those who did not give consent. Results: Out of 51 elderly patients, males accounted for 55%, females accounted for 45% and a  gender ratio of 1.2:1 for male to female. Among 51 patients with new-onset seizures, hypertension was seen in 29.4% patients as co-morbidity  and 13.7% patients had both hypertension and diabetes as co-morbidities. The study also showed that generalized tonic-clonic seizures (GTCS)  were found among 76.5% cases whereas among 23.5% patients were of focal seizures. However, acute and remote symptomatic were almost  found in an equal proportion 47.1% and 45.2% respectively and only 7.8% were idiopathic. It was noted that the maximum number of patients  had CVA as the cause of new onset seizures in this age group, of which 90.9% patients had an ischaemic stroke. 14 patients had metabolic  insult of which, 35.71% patients had uremic encephalopathy as the cause of new onset seizures. 60% of seizures in CNS infections are  secondary to tuberculosis probably because of high burden of tuberculosis in the study area. Conclusion: In our study CVA was the frequently  observed etiology of seizures among study population and the second most common was metabolic insults. Among stroke, seizures occured  more commonly in ischemic stroke than in hemorrhagic stroke. In our study GTCS was the most common type of seizure in 76.5% of study  population. And acute symptomatic and remote symptomatic were almost seen in equal numbers 47.1% and 45.2% respectively. CVA  accounted for most of the remote symptomatic seizures of which ischemic stroke is most common and metabolic causes accounted for most of  the acute symptomatic seizures. The high burden of tuberculosis in the study area may have accounted for this higher percentage (60%) of  seizures secondary to tuberculosis in the study patients under CNS infections sub group.
Keywords: Seizures; Epilepsy; Geriatric Population